A socio-cultural and comparative analysis of the doctrine of mistake in crimes requiring intention - Wolhuter, Lorraine (Institute of Criminology, 2021)
Academics have often been criticised for their preoccupation with theoretical abstraction and logical deduction and their concomitant failure to address issues of practical importance or exigency. It must therefore be stated at the outset that the recommendations contained in this paper are not confined to a theoretical analysis of the doctrine of mistake. Per contrast, they are motivated by a genuine concern on the part of the writer to alleviate the present discord between South African criminal legal theory and socio-cultural reality. These recommendations are premised upon the advantages of the reception of the normative approach to criminal liability in South Africa, and they have been iterated elsewhere l by the writer in the context of, inter alia, the defence of necessity. The submissions that constitute the core of this paper must, however, be regarded as subject to the following qualification. A successful reception of the normative approach necessitates a change in the existing power relations that are operative in South African courts. To leave its application to the presiding judge and assessors would be to give them the freedom to inflect their decisions with their personal values and prejudices. It has been argued elsewhere2 by the writer that this problem may possibly be solved by the reintroduction of the jury system, suitably loaded to cater for the interests operative in the case. Sustained reflection and exposure to the exigencies of practice has, however, yielded the conclusion that the difficulties that accompanied the jury system and the suspicion with which it was viewed, outweigh any advantages that its re-introduction may have. A possible alternative, and one which, it is submitted, would work well in practice, is the increased use of expert witnesses at the stage prior to conviction, provided that they are suitably qualified (either formally or informally) to adduce evidence on the socio-cultural matrix of relations in which the accused in question lives and moves. In the context of mistake of law, for example, evidence concerning, inter alia, the level of legal knowledge and general education in a particular community could be adduced by persons who are either long-standing members or active participants in the socio-cultural life. of such community. The theoretical views and preferences expressed in this paper should thus be read with the above-mentioned practico-social problems in mind.